Dietary supplementation with Chinese herb ultrafine powder improves intestinal morphology and physical barrier function by altering jejunal microbiota in laying hens - Gui, Jue; Azad, Md Abul Kalam; Lin, Wenchao; Meng, Chengwen; Hu, Xin; Cui, Yadong; Lan, Wei; He, Jianhua; Kong, Xiangfeng (Frontiers in Microbiology, 2023)
Introduction Chinese medicinal herbs play important roles in anti-inflammatory, antioxidant, and antibacterial activities. However, the effects of Chinese herb ultrafine powder (CHUP) on laying hens still need to be elucidated. Therefore, this study aimed to evaluate the effects of dietary CHUP supplementation on jejunal morphology, physical barrier function, and microbiota in laying hens. Methods A total of 576 Xinyang black-feather laying hens (300 days old) were randomly assigned into eight groups, with eight replicates per group and nine hens per replicate. The hens were fed a basal diet (control group) and a basal diet supplemented with 0.5% Leonuri herba (LH group), 0.25% Ligustri lucidi fructus (LF group), 0.25% Taraxaci herba (TH group), 0.5% LH + 0.25% LF (LH-LF group), 0.5% LH + 0.25% TH (LH-TH group), 0.25% LF + 0.25% TH (LF-TH group), and 0.5% LH + 0.25% LF + 0.25% TH (LH-LF-TH group), respectively, for 120 days. Results The results showed that dietary LH-LF and LH-LF-TH supplementation increased (p < 0.05) the jejunal villus height to crypt depth ratio of laying hens. Dietary LF-TH supplementation up-regulated jejunal claudin-5 expression, while LH supplementation up-regulated jejunal claudin-1 expression and increased the jejunal abundances of potentially beneficial bacteria related to short-chain fatty acids and bacteriocins production, such as Blautia, Carnobacterium, Clostridiales, and Erysipelotrichales (p < 0.05). In addition, dietary LH supplementation enriched (p < 0.05) the tetracycline biosynthesis, butirosin/neomycin biosynthesis, and D-arginine/D-ornithine metabolism, whereas steroid biosynthesis and limonene/pinene degradation were enriched (p < 0.05) in the LH-LF and LH-LF-TH groups. Moreover, Spearman’s correlation analysis revealed the potential correlation between the abundance of the jejunal microbiota and jejunal morphology and the physical barrier function of laying hens. Discussion Collectively, these findings suggest that dietary CHUP supplementation could enhance the beneficial bacteria abundance, physical barrier function, and metabolic function associated with short-chain fatty acids and bacteriocins production. Moreover, combined supplementation of dietary CHUP showed better effects than the sole CHUP supplementation.